TRANSFORMASI ORNAMEN KOUTOUBIA DAN PENERAPAN FLOUNCE SERTA BORDIR PADA BUSANA AVANT GARDE - Wina Rosmalia Dewi; Ratna Suhartini (Practice of Fashion and Textile Education Journal, 2026)
This study aims to describe the process of transforming the architectural ornaments of the Koutoubia Mosque into avant-garde fashion designs through the application of fabric manipulation techniques (flounce and embroidery), and to describe the final avant-garde garments resulting from the transformation of the Koutoubia Mosque ornaments using fabric manipulation techniques. The Double Diamond method consists of four stages: discover, define, develop, and deliver. In the discover stage, sources of inspiration were explored. The define stage involved the development of visual concepts and sources of inspiration. The develop stage included design development and the realization process. The deliver stage represented the final phase of the overall design process. Data were obtained using observation sheets assessed by three fashion experts, based on the Guttman scale and analyzed descriptively. The observation results showed that the transformation process of ornaments through flounce manipulation achieved 66.6% because the source of inspiration still needed further exploration, whereas embroidery was successfully transformed, reaching 100%. The avant-garde fashion outcomes in terms of design elements, design principles, and avant-garde characteristics achieved 100% success in representing the architectural ornaments of the Koutoubia Mosque into avant-garde fashion designs using fabric manipulation techniques of flounce and embroidery. Keywords : Koutoubia Mosque Ornaments, Avant-Garde, Flounce, Embroidery